An IIoT Edge Environment as a Main Support to a 3D Reconstruction Virtualization Application - Badat, Leya; Vidal, Vinicius; Pioli, Laércio; Mehaut, Jean-Francois; Honorio, Leonardo; Dantas, Mario Antonio Ribeiro (Anais do Workshop em Clouds e Aplicações (WCGA); 2020: Anais do XVIII Workshop em Clouds e AplicaçõesDO - 10.5753/wcga.2020.12440, 2020)
This paper describes an experimental research work, which was conducted to gather different types of cameras and computer node, as IIoT (Industrial IoT) devices, to produce support to a digital transformation with a 3D reconstruction virtualization for a real engineering application. The computational approach considered was a heterogeneous edge computing environment. In this environment, different cameras and computer node architectures, collaborate as heterogeneous IIoT processing elements, to provide a better, and as fast as possible, images to a virtualization project. The challenge and complexity related to software packages orchestration, from these IIoT devices, are also reported.